DEVELOPMENT OF MICRO-MOBILITY MODES TO SUPPORT FIRST AND LAST MILE CONNECTIVITY IN THE PUBLIC TRANSPORTATION SYSTEM OF SURAKARTA CITY - Muhammad Fadhil Athallah; Santy Paula Dewi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Micro mobility has an important role in improving first–last mile (FLM) connectivity as a link between community activities and the public transportation system. In the city of Surakarta, the low use of public transportation is still driven by the low quality of accessibility to transportation nodes and variations in the performance of micromobility services. This study aims to analyze FLM's travel characteristics, user perceptions and preferences towards micromobility services, and identify priority service attributes that need to be optimized to support integration with public transportation. The research method used descriptive analysis, instrument validity and reliability tests, and Importance–Performance Analysis (IPA) applied to four micro mobility modes: pedicabs, walking, bicycles, and electric scooters. A total of 213 respondents who met the criteria participated in the survey. The results showed that all service attributes have a negative gap between importance and performance levels, so users judge that the current service quality does not meet FLM's travel needs. The analysis of IPA per mode shows that the main priority attributes include travel safety and security, the availability of protected lanes, supporting facilities, accessibility to public transportation nodes, and the availability of travel information. These findings confirm that the success of the integration of micro mobility and public transportation in Surakarta is highly dependent on improving the quality of basic facilities, protecting users' movement space, and strengthening access infrastructure support.